RISIKO HARGA DAN RISIKO PRODUKSI USAHATANI RUMPUT LAUT DI KECAMATAN POLEWALI KABUPATEN POLEWALI MANDAR - Muhammad Nur Alamsyah Ali; Syafiuddin Syafiuddin; Sri Mardiyati; Mohammad Natsir; Nurdin Nurdin (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2026)
This study examines production and price risks in seaweed farming in Polewali District, Polewali Mandar Regency, which influence farmers' income uncertainty. The study aimed to identify and quantify the level of production and price risks. The method used was a quantitative approach with primary and secondary data, as well as descriptive statistical analysis through the mean, standard deviation, and coefficient of variation (CV). The sample was determined by simple random sampling of 32 farmers. The results showed that production risk was high (CV = 0.80) due to environmental factors and disease attacks, while price risk was low (CV = 0.09) due to relatively stable prices. These findings contribute to the development of basic education, particularly in contextual learning based on real-world problems in the agribusiness sector.